Exploring pluriliteracy as theory and practice in multilingual/cultural contexts - Koo, Yew Lie (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
This paper is situated in language and literacy studies (Gee 1996) and Malaysian Studies (Tan,1992; Shamsul, 1999;Maznah and Wong, 2001; Ooi, 2001) and explores what I theorise to be the pluriliteracy (Koo 2004) of Malaysian tertiary leamers in relation to the discourses of the community, nation-state and globalisation. It takes the perspective of linguistic practices as involving culture (as interpretive systems of meaning involving webs of significance (Geertz,1973) and linguistic processes as sociocultural practice (Kress, 1989). The pluriliteracy of the multilingual meaningmakers in English is viewed in terms of a third space phenomenon (Bhabha, 1994) a deep sociopolitical space marked by power and ideological divides.Pluriliteracy views meaning-making and knowledge production as sociopolitical phenomena involving decisions and reflections around the ideological embeddings of dominant cultures. The third space is a complex and challenging space fraught with tensions for the multilingual learner,where various literacies are accommodated, nativised and transformed within the intersection and contradictions of community, national and global discourses. The paper explores the concept of Reflexive Pluriliteracy in two ways: firstly, by examining the broad sociopolitical contexts of Malaysia viewed as the intersection of the global with the nation-state and secondly, by examining the micro meaning making literacy practices of two Malaysian meaning-makers, Su and Beng. The broad and the micro are viewed as interpenetrating discursive discourses each interacting with the other. In exploring the extant pluriliteracies of multilingual meaning-makers as unfolding and as learned behavior, the paper argues for a pedagogy of reflexive Pluriliteracy. It is argued that reflexive pluriliteracy will help provide a greater awareness of the politics and tensions in various ways of knowing, in the third space of the simultaneously local-global, with its tensions and ambivalence.